First detection of the equine herpesvirus 1 neuropathogenic variant in Brazil - Mori, E.; Borges, Alexandre Secorun [UNESP]; Delfiol, D. J. Z. [UNESP]; Oliveira Filho, José Paes de [UNESP]; Goncalves, Roberto Calderon [UNESP]; Cagnini, Didier Quevedo [UNESP]; Lara, M. C. C. S. H.; Cunha, E. M. S.; Villalobos, E. M. C.; Nassar, A. F. C.; Castro, A. M. M. G.; Brandao, P. E.; et al. (Office Int Epizooties, 2011)
This report describes the first detection of an equine herpesvirus 1 (EHV-1) neuropathogenic variant (G(2254)/D-752) in Brazil from a case of fatal equine herpesvirus myeloencephalopathy (EHM) in a mare. The results of nucleotide sequencing of the EHV-1 ORF30 gene showed that two other Brazilian EHV-1 isolates from EHM cases are representatives of the non-neuropathogenic variant (A(2254)/N-752), suggesting that other unidentified factors are probably also involved in the neuropathogenicity of EHV-1 in horses. These findings will contribute to the epidemiological knowledge of EHV-1 infection in Brazil.
Keywords: Brazil; DNA polymerase gene; Equine herpesvirus 1; Neurological disease; Neuropathogenic